Progress in Pattern Recognition, Image Analysis, Computer Vision, and Applications 17th Iberoamerican Congress, CIARP 2012, Buenos Aires, Argentina, September 3-6, 2012. Proceedings - Alvarez, Luis.; Mejail, Marta; Gomez, Luis.; Jacobo, Julio; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 17th Iberoamerican Congress on Pattern Recognition, CIARP 2012, held in Buenos Aires, Argentina, in September 2012. The 109 papers presented, among them two tutorials and four keynotes, were carefully reviewed and selected from various submissions. The papers are organized in topical sections on face and iris: detection and recognition; clustering; fuzzy methods; human actions and gestures; graphs; image processing and analysis; shape and texture; learning, mining and neural networks; medical images; robotics, stereo vision and real time; remote sensing; signal processing; speech and handwriting analysis; statistical pattern recognition; theoretical pattern recognition; and video analysis.
Face and iris: detection and recognition -- clustering; fuzzy methods -- human actions and gestures -- graphs; image processing and analysis -- shape and texture -- learning, mining and neural networks -- medical images -- robotics, stereo vision and real time -- remote sensing -- signal processing -- speech and handwriting analysis -- statistical pattern recognition -- theoretical pattern recognition -- video analysis.
Keywords: Computer science; Computer software; Artificial intelligence; Computer vision; Optical pattern recognition; Biometrics; Computer Science; Pattern Recognition; Image Processing and Computer Vision; Artificial Intelligence (incl. Robotics).; Biometrics; Algorithm Analysis and Problem Complexity; Information Systems Applications (incl. Internet).